Clinical outcomes of peripartum fibrinogen replacement plus tranexamic acid in congenital hypofibrinogenemia: a single-centre case series of eight pregnancies - Jing Tian; Tianying Zhu; Terence T. Lao; Min Xie; Yunping Wu; Runmei Ma (Blood Coagulation & Fibrinolysis, 2026)
Pregnancy in congenital hypofibrinogenemia is rare and hemorrhage-prone, with no reported use of tranexamic acid (TXA). We retrospectively reviewed eight pregnancies in six women (2015–2025). One intrauterine fetal death occurred. Seven live births were complicated by preterm membrane rupture, placental abruption, and postpartum hemorrhage (PPH; 4/8). All received peripartum fibrinogen replacement; seven also received intravenous TXA (1–3 g). Despite predelivery fibrinogen